2001
DOI: 10.1093/jexbot/52.357.747
|View full text |Cite
|
Sign up to set email alerts
|

Further observations on the interaction between sugar cane and Gluconacetobacter diazotrophicus under laboratory and greenhouse conditions1

Abstract: Sugar cane (Saccharum spp.) variety SP 70-1143 was inoculated with Gluconacetobacter diazotrophicus strain PAL5 (ATCC 49037) in two experiments. In experiment 1 the bacteria were inoculated into a modified, low sucrose MS medium within which micropropagated plantlets were rooted. After 10 d there was extensive anatomical evidence of endophytic colonization by G. diazotrophicus, particularly in lower stems, where high numbers of bacteria were visible within some of the xylem vessels. The identity of the bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
1
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 4 publications
5
67
1
6
Order By: Relevance
“…Several studies have shown that endophytic populations of strains of various nonpathogenic bacterial species cannot become established following infiltration into leaves (48,69). To our knowledge, only James et al (21,23) have reported colonization of substomatal chambers by plantbeneficial bacteria, but there was the possibility of epiphytic bacterial propagation on the phylloplane (21,23) and/or spreading within the plant (23). Our finding of PsJN cells in substomatal chambers after an initial root colonization step confirmed that substomatal chambers can be colonized by bacteria after they spread within the plant.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have shown that endophytic populations of strains of various nonpathogenic bacterial species cannot become established following infiltration into leaves (48,69). To our knowledge, only James et al (21,23) have reported colonization of substomatal chambers by plantbeneficial bacteria, but there was the possibility of epiphytic bacterial propagation on the phylloplane (21,23) and/or spreading within the plant (23). Our finding of PsJN cells in substomatal chambers after an initial root colonization step confirmed that substomatal chambers can be colonized by bacteria after they spread within the plant.…”
Section: Discussionsupporting
confidence: 77%
“…The bacteria are able to infect and colonize the root tissues and aerial parts by penetrating root tip and lateral roots formed during the rooting process (James et al 1994). At the colm base, where the tissues are heavily colonized, the bacteria move to the aerial part using the xylematic vessels (James et al 1994(James et al , 2001. Relatively large populations of the bacteria are found in these tissues, suggesting that this is one of the main sites for nitrogen fixation due to the low oxygen level and the energy available in form of sucrose for nitrogen fixation (James et al 1994).…”
Section: Inoculation Responsementioning
confidence: 99%
“…Accumulation of polysaccharides and tannins in the parenchyma cells around the metaxylem of sugarcane clone Ja60-5 inoculated with Gluconacetobacter diazotrophicus has also been observed, suggesting that the plant defense system is activated during the interaction with the bacterium (Dong et al, 1997). In sugarcane cultivar SP70-1143, no hypersensitive response has been observed after inoculation of leaves and stems with G. diazotrophicus, although an extracellular matrix accumulates around bacterial cells in the protoxylem and xylem parenchyma (James et al, 2001).…”
Section: Introductionmentioning
confidence: 99%